"High-grade oncocytic renal tumor": morphologic, immunohistochemical, and molecular genetic study of 14 cases. - He, Huiying; Trpkov, Kiril; Martinek, Petr; Isikci, Ozlem Tanas; Maggi-Galuzzi, Cristina; Alaghehbandan, Reza; Gill, Anthony J; Tretiakova, Maria; Lopez, Jose Ignacio; Williamson, Sean R.; Montiel, Delia Perez; Sperga, Maris; et al. (Virchows Archiv: European Journal of Pathology, 2018)
The spectrum of the renal oncocytic tumors has been expanded in recent years to include several novel and emerging entities. We describe a cohort of novel, hitherto unrecognized and morphologically distinct high-grade oncocytic tumors (HOT), currently diagnosed as "unclassified" in the WHO classification. We identified 14 HOT by searching multiple institutional archives. Morphologic, immunohistochemical (IHC), molecular genetic, and molecular karyotyping studies were performed to investigate these tumors. The patients included 3 men and 11 women, with age range from 25 to 73 years (median 50, mean 49 years). Tumor size ranged from 1.5 to 7.0 cm in the greatest dimension (median 3, mean 3.4 cm). The tumors were all pT1 stage. Microscopically, they showed nested to solid growth, and focal tubulocystic architecture. The neoplastic cells were uniform with voluminous oncocytic cytoplasm. Prominent intracytoplasmic vacuoles were frequently seen, but no irregular (raisinoid) nuclei or perinuclear halos were present. All tumors demonstrated prominent nucleoli (WHO/ISUP grade 3 equivalent). Nine of 14 cases were positive for CD117 and cytokeratin (CK) 7 was either negative or only focally positive in of 6/14 cases. All tumors were positive for AE1-AE3, CK18, PAX 8, antimitochondrial antigen, and SDHB. Cathepsin K was positive in 13/14 cases and CD10 was positive in 12/13 cases. All cases were negative for TFE3, HMB45, Melan-A. No TFEB and TFE3 genes rearrangement was found in analyzable cases. By array CGH, complete chromosomal losses or gains were not found in any of the cases, and 3/9 cases showed absence of any abnormalities. Chromosomal losses were detected on chromosome 19 (4/9), 3 with losses of the short arm (p) and 1 with losses of both arms (p and q). Loss of chromosome 1 was found in 3/9 cases; gain of 5q was found in 1/9 cases. On molecular karyotyping, 3/3 evaluated cases showed loss of heterozygosity (LOH) on 16p11.2-11.1 and 2/3 cases showed LOH at 7q31.31. Copy number (CN) losses were found at 7q11.21 (3/3), Xp11.21 (3/3), Xp11.22-11.21 (3/3), and Xq24-25 (2/3). CN gains were found at 13q34 (2/3). Ten patients with available follow up information were alive and without disease progression, after a mean follow-up of 28 months (1 to 112 months). HOT is a tumor with unique morphology and its IHC profile appears mostly consistent. HOT should be considered as an emerging renal entity because it does not meet the diagnostic criteria for other recognized eosinophilic renal tumors, such as oncocytoma, chromophobe renal cell carcinoma (RCC), TFE3 and TFEB RCC, SDH-deficient RCC, and eosinophilic solid and cystic RCC.